Depth of Moist Soil at Planting Affected Grain Sorghum Response to Nitrogen Fertilizer - Augustine K. Obour; John D. Holman; Yared Assefa Mulisa (Kansas Agricultural Experiment Station Research Reports, 2023)
The depth of moist soil before planting is a critical factor for grain crop production in dryland cropping systems. We investigated depth of moist soil at planting and nitrogen (N) fertilizer application effects on continuous grain sorghum yields on a Crete silt loam soil over 32 years in western Kansas. Treatments were four N rates (0, 20, 40, and 60 lb/a) in a randomized complete block design with four replications and depth of moist soil at planting determined with a Paul Brown moisture probe. Grain sorghum yield response to N fertilizer application was -0.10, 14.4, 29.3, and 36.5 lb of grain/a for every lb of N applied in very low yielding (VLY), low yielding (LY), high yielding (HY), and very high yielding (VHY) environments, respectively. Grain yield increased with depth of moist soil at planting for each N rate, with yield increases of 217 to 461 lb/a per inch increase in depth of moist soil at planting for the unfertilized control through 60 lb N/a. Regardless of yield environment, net returns were negative when depth of moist soil at planting was less than 30 inches. These results suggest that continuous grain sorghum should not be planted when depth of moist soil measured with a Paul Brown probe is<30 inches. Results of this 32-year study showed the depth of moist soil at planting could be used to fine-tune N application rates for sorghum. Despite greater drought tolerance, sorghum N response is dependent on combination of soil water at planting and in-season precipitation. We need to continue this research to identify sorghum hybrids with improved drought tolerance and nitrogen use efficiency to increase probability of dryland sorghum production.
Keywords: Grain sorghum; plant available water; nitrogen; dryland